2020
DOI: 10.1155/2020/8703627
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clopidogrel in 2020: A Reappraisal

Abstract: Antiplatelet therapy is the mainstay of treatment and secondary prevention of cardiovascular disease (CVD), including acute coronary syndrome (ACS), transient ischemic attack (TIA) or minor stroke, and peripheral artery disease (PAD). The P2Y12 inhibitors, of which clopidogrel was the first, play an integral role in antiplatelet therapy and therefore in the treatment and secondary prevention of CVD. This review discusses the available evidence concerning antiplatelet therapy in patients with CVD, with a focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 116 publications
1
57
0
6
Order By: Relevance
“…Ticagrelor, with its better safety profile, should be considered over clopidogrel in most ACS patients. Although, current observational studies reporting inconsistent results do not confirm the superiority of newer P2Y 12 inhibitors over clopidogrel in ACS patients receiving PCI 51 , they are prone to bias and should be interpreted with caution given the potential for confounding. Nevertheless, real-world studies are helpful in translating the findings from RCTs into practice settings in the general population.…”
Section: Discussionmentioning
confidence: 94%
“…Ticagrelor, with its better safety profile, should be considered over clopidogrel in most ACS patients. Although, current observational studies reporting inconsistent results do not confirm the superiority of newer P2Y 12 inhibitors over clopidogrel in ACS patients receiving PCI 51 , they are prone to bias and should be interpreted with caution given the potential for confounding. Nevertheless, real-world studies are helpful in translating the findings from RCTs into practice settings in the general population.…”
Section: Discussionmentioning
confidence: 94%
“…Some patients can also develop recurrent ischemic events such as stent thrombosis and myocardial infarction during treatment with clopidogrel. This failure of platelet aggregation inhibition in clopidogrel users is referred to as clopidogrel resistance (CR) or platelet hyperresponsiveness [ 11 , 12 , 13 ]. Studies have shown that 4 to 30% of patients have CR, and 5 to 6% of patients have DAPT resistance after implanting the stent [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HTPR are known to present with a significantly higher risk of CV death, MI, and ST post-PCI (Aradi et al, 2010). Despite many disadvantages of clopidogrel administration, newer P2Y12 inhibitors-prasugrel and ticagrelor, often come with increased risk of bleeding, which in some patients, leads to the need to de-escalate the therapy with clopidogrel (Patti et al, 2020). Thus, monitoring of patients on DAPT with clopidogrel, more comprehensive understanding of interindividual difference in response to clopidogrel treatment, together with more advanced platelet-function monitoring techniques, could be beneficial in the prevention of adverse thrombotic outcomes (Aradi et al, 2010).…”
Section: Mirna Expression In Patients Receiving Dapt-focus On Asa Andmentioning
confidence: 99%